2013
DOI: 10.1007/s00701-013-1854-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new neurological score (FOUR Score) in the assessment of neurosurgical patients with severely impaired consciousness

Abstract: The FOUR score was more robust than the GCS in predicting mortality after 30 days in neurosurgical patients with severely impaired consciousness. There was no relevant difference in predicting poor and good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 32 publications
1
41
0
1
Order By: Relevance
“…FOUR better classifies level of consciousness damage in emergency patients (15,16), cardiac arrest patients (8), and ICU patients (12) compared to other scales. Furthermore, FOUR has greater validity and reliability among nurses, neurologists, and doctors (5,6,11,20). In the present study, FOUR showed high predicting value for in-hospital mortality, which agreed with Sadaka study (19).…”
Section: █ Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FOUR better classifies level of consciousness damage in emergency patients (15,16), cardiac arrest patients (8), and ICU patients (12) compared to other scales. Furthermore, FOUR has greater validity and reliability among nurses, neurologists, and doctors (5,6,11,20). In the present study, FOUR showed high predicting value for in-hospital mortality, which agreed with Sadaka study (19).…”
Section: █ Resultsmentioning
confidence: 99%
“…Brain stem reflexes facilitate assessment of midbrain, pons and medulla oblongata functioning (18). This scale assesses various levels of damage to brain stem, and provides more accurate clinical prognosis for patient outcomes (5). Meanwhile, these are not examined in GCS scale.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pemeriksaan terhadap posisi tangan telah divalidasi sebelumnya dan dianggap reliabel untuk mendeteksi perubahan kesadaran sangat minimal. [13][14][15] Pemeriksaan refleks batang otak dapat membantu dalam penilaian kedalaman koma yang lebih lengkap dan akurat. Pemeriksaan fungsi batang otak, seperti refleks cahaya pupil, refleks kornea, dan refleks batuk dapat menilai fungsi mesensefalon, pons, medula oblongata, dan saraf okulomotor.…”
Section: Komponen Penilaian Pada Four Scoreunclassified